Research note: Understanding the relationship between service quality, service outcomes, and satisfaction in the spa industry - Sivanun SIVAPITAK; Aswin SANGPIKUL (Tourism and Hospitality Management)
Purpose – In a spa setting, customers expect to receive service outcomes (feeling better of well-being) after the service consumption. Service outcomes are important as they can affect customer satisfaction and repeat consumption in the spa industry. However, there is a scarcity of empirical studies to fully understand their relationships with service quality and customer satisfaction in the spa context. This research, therefore, has an objective to investigate the relationships between service quality, service outcomes, and satisfaction in the spa industry by using Thailand setting. Methodology/Design/Approach – Data were collected from 249 spa customers through a convenience sampling. Path analysis and structural equation modelling analysis (SEM) were used to test the relationship and the structural model. Findings – The study found positive relationships between service quality, service outcomes, and customer satisfaction. In particular, service outcomes were found to partially mediate the relationship between service quality and satisfaction. Interestingly, the influence of service outcomes (a mediator) on customer satisfaction was greater than service quality alone, suggesting another determinant of customer satisfaction in the spa industry. It was also found that service outcomes had a special feature because they were influenced by service quality, meanwhile, they also affected customer satisfaction. Originality of the research – This is the first empirical study to fully examine the relationships between service quality, service outcomes, and satisfaction in the spa industry. The study makes a significant contribution to the spa literature by verifying the special characteristics (roles) of service outcomes and their relationship with service quality and customer satisfaction.